Compassion Satisfaction, Burnout, and Secondary Traumatic Stress among Respiratory Therapists in Mississippi: A Cross-Sectional Study - Driscoll DeVaul; Britney Reulet; Jacob Daniels; Xiaoqian Zhu; Renee Wilkins; Xiaoshan Z. Gordy (MDPI AG, 2023)
The COVID-19 pandemic had an immense effect on the well-being of healthcare professionals. In this study, researchers utilized a quantitative cross-sectional study design to investigate the degree of compassion satisfaction and fatigue amongst respiratory therapists in the state of Mississippi as a result of providing care to patients during the COVID-19 pandemic. Quantitative data were collected using an anonymous online survey that assessed the well-being and satisfaction of licensed respiratory therapists in the state of Mississippi. More specially, survey responses (n = 326) were quantitatively evaluated to measure the association between demographic variables and compassion satisfaction (CS), burnout (BO), and secondary traumatic stress (STS). Ninety-seven percent of participants reported a medium to high CS level, while 74% indicated having a medium to high level of BO, and 69% reported a medium to high level of STS. Neither age nor gender had a significant difference in CS (p = 0.504; p = 0.405), BO (p = 0.161; p = 0.285), or STS (p = 0.145; p = 0.252). Those working for more than 10 years at their current employer had higher CS (M = 38.7) and lower BO (M = 24.9) and STS (M = 24.8) scores. The number of hours worked, specifically overtime, had a significant impact on BO (β = 0.09, p = 0.028) and STS (β = 0.0.11, p = 0.019), but not CS (β = 0.02, p = 0.655). These findings suggest that the number of years employed in the field impacts the level of compassion satisfaction and contributes to lower levels of burnout and secondary traumatic stress. The age of a patient may also affect levels of compassion and burnout. The results of this study highlight the importance of developing incentive plans in an effort to retain employees.